EVALUASI PELAKSANAAN KOTA LAYAK ANAK DALAM PENYEDIAAN INFRASTRUKTUR (SARANA DAN PRASARANA) RAMAH ANAK DI KOTA PADANG - nurul annisa; Zikri Alhadi (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2019)
This research aim to examine how the provision of child friendly infrastructure (facilities and infrastructure) in the city of Pariaman. For this reason, an evaluation is needed to assess the policy,based on William Dunn’s theory, there are 6 criteria, effectiveness, efficiency, adequency, flattening,responsiveness and accuracy. And the measure had taken by the government institution on issues of the provision of child friendly infrastructure (facilities and infrastructure) at Pariaman city. This research is qualitative descriptive. Data sources from primary and secondary. Data collection techniques are observation, interview and documentation. Test the validity of data checking through triangulation. The findings problem of field, the provision of child friendly infrastructure Pariaman was good but not maximal. It was seen since the time child friendly was implemented, Pariaman still remains in the middle position.